The effect of employee motivation on employee practices - Namugalu shalom joy (Uganda Christian university, 2024)
This research report was undertaken to investigate the effect of employee performance on motivational practices in Mukono district local government. It was guided by three objectives; to examine the effect of employee engagement on motivational practices ABSTRACT of Mukono district local government, to determine the effect of employee job satisfaction on motivational practices of Mukono district local government, to explore the effect of employee autonomy on motivational practices of Mukono district local government. The researcher used a sample size of 63 respondents and used questionnaires and interview guide to collect data and later the data was analyzed using the statistical package for social sciences (SPSS). Results of the first objective showed that employee performance has a significant effect in Mukono district local government.. Supported by the following responses; 54% of the respondents were positive to the statement that high employee performance leads to increased productivity and efficiency in achieving organizational goals; 62% were positive to the statement that high performance often improves morale and job satisfaction, reducing turnover. Results of the second objective revealed that a motivational practice has a significant effect in Mukono district local government. Supported by the following responses; 56% of the respondents were positive to the statement that motivational practices boost employee morale, leading to enhanced productivity and performance, 80% of the respondents were positive to the statement effective motivation increases employee job satisfaction, making them more committed to their roles, it can be observed that 57% were positive to the statement that motivation fosters greater engagement, leading to better focus and dedication toward work. Mukono district local government should provide continuous training and development programs to equip employees with the necessary skills for their roles. Clear communication of expectations and goals, along with regular feedback and recognition for good performance, fosters motivation. Creating a supportive and inclusive workplace culture, where employees feel valued and empowered to contribute, can further enhance performance. Additionally, offering opportunities for career growth and ensuring work-life balance helps t
This research was written to motivate employees in uganda